Х - второе число, (х + 3) - первое число. Уравнение: 3/8 * (х + 3) = 4/9 * х 3/8х + 9/8 = 4/9х 9/8 = 4/9х - 3/8х 9/8 = 32/72х - 27/72х 9/8 = 5/72х х = 9/8 : 5/72 х = 9/8 * 72/5 х = 81/5 х = 16,2 - второе число 16,2 + 3 = 19,2 - первое число ответ: числа 19,2 и 16,2.
Х - второе число, (х + 3) - первое число. Уравнение: 3/8 * (х + 3) = 4/9 * х 3/8х + 9/8 = 4/9х 9/8 = 4/9х - 3/8х 9/8 = 32/72х - 27/72х 9/8 = 5/72х х = 9/8 : 5/72 х = 9/8 * 72/5 х = 81/5 х = 16,2 - второе число 16,2 + 3 = 19,2 - первое число ответ: числа 19,2 и 16,2.
Х=21-12
Х=9:3
Х=3
3•(6-3)+12=21
Пошаговое объяснение: